Pluriversos : un camino hacia la construcción de contra tendencias desde lo popular (2017)
"Pluriversos is a new way of trend forecasting and trend research, based on Latin-American popular culture. It tries to understand the local behaviours and aesthetics and it questions in order to understand which is its value in the international scenario. It works with people who lives in Bogota's popular contexts as the principal research and design tool. Pluriversos also questions the way in which trend forecasting researches, it questions cool hunting and the cool hunter as the main tool in a trend research. It sees to expand and enrich the aesthetics and behaviours that are considerate as a trend, making visible what happens in new an different places (spaces) as the popular culture in Bogotá." -- Tomado del Formato de Documento de Grado.